Aptamer Detection of Mycobaterium tuberculosis Mannose-Capped Lipoarabinomannan in Lesion Tissues for Tuberculosis Diagnosis - Zhou, Yuanyuan; Xiong, Huan; Chen, Rong; Wan, Lixia; Kong, Ying; Rao, Jianwei; Xie, Yan; Huang, Chaolin; Zhang, Xiao-Lian (Frontiers in Cellular and Infection Microbiology, 2021)
Tuberculosis (TB) is the leading infectious cause of mortality worldwide. However, the diagnosis of TB, especially extrapulmonary TB (EPTB) diagnosis from lesion tissues, remains a challenge. Nucleic acid aptamers are analogous to antibodies and have advantages of easier modification, high specificity and affinity. Mannose-capped lipoarabinomannan (ManLAM) is a unique surface lipoglycan component or constantly released from mycobacterium tuberculosis (M.tb) cell wall, which makes it a perfect candidate biomarker for TB diagnosis. Our present study aims to establish M.tb ManLAM aptamer-based immunohistochemistry (IHC) method for TB diagnosis. We performed TB diagnosis using 263 formalin-fixed paraffin-embedded tissue samples including 213 TB samples (pulmonary TB (PTB) and EPTB), and 8 samples from latent TB infection (LTBI) high risk subjects, and 42 samples from other non-TB patients with ManLAM aptamer-based IHC and routine laboratory TB diagnostic methods parallelly. The sensitivity and specificity of the ManLAM aptamer-based IHC were 86.38% and 92.86%, with much higher sensitivity than those of mycobacterial culture (9.66%) and acid-fast staining (AFS) (43.01%) and comparability to Interferon-gamma Release Assay (IGRA) (84.38%) and GeneXpert (79.31%). High agreement between ManLAM based-IHC and IGRA or GeneXpert for TB diagnosis were observed. Furthermore, ManLAM aptamer-based IHC combination with other routine TB laboratory diagnostic methods significantly increased the sensitivity up to 88.64%-97.92%. As our knowledge, this is the first report about aptamer-based IHC for disease diagnosis. Thus, ManLAM aptamer-based IHC has potentials for TB diagnosis, including PTB, and EPTB, and assists the diagnosis of LTBI with high effectiveness, feasibility and easy production.